2018
DOI: 10.1016/j.neuron.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Changes in Either Criterion or Sensitivity Are Associated with Robust Modulations in Lateral Prefrontal Cortex

Abstract: Visual attention is associated with neuronal changes across the brain, and these widespread signals are generally assumed to underlie a unitary mechanism of attention. However, using signal detection theory, attention-related effects on performance can be partitioned into changes in either the subject's criterion or sensitivity. Neuronal modulations associated with only sensitivity changes were previously observed in visual cortex, raising questions about which structures mediate attention-related changes in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 67 publications
3
67
3
Order By: Relevance
“…The latency for generating rewarded motor actions was slower in KO versus WT mice, despite stimuli appearing at the same locations and same visual contrast ranges across experiments. Recent studies of visual perception using detection tasks have shown that both changes in sensitivity and response criterion contribute to perceptual performance, and that these two components of perception are dissociable with appropriate tasks and likely driven by distinct brain structures (Luo & Maunsell, 2018). Our results here in KO mice identify elevation of response criterionthe internal threshold to report detection-as one key component of behavioral impairments in KO mice.…”
Section: Discussionsupporting
confidence: 51%
“…The latency for generating rewarded motor actions was slower in KO versus WT mice, despite stimuli appearing at the same locations and same visual contrast ranges across experiments. Recent studies of visual perception using detection tasks have shown that both changes in sensitivity and response criterion contribute to perceptual performance, and that these two components of perception are dissociable with appropriate tasks and likely driven by distinct brain structures (Luo & Maunsell, 2018). Our results here in KO mice identify elevation of response criterionthe internal threshold to report detection-as one key component of behavioral impairments in KO mice.…”
Section: Discussionsupporting
confidence: 51%
“…D. Proportion of change events at each location in a block with high cue validity (left) and in a block with neutral cues (right). Red: Cued location; green: location opposite to cue (Opp); blue: location adjacent to cue, either in the same visual hemifield as cue (Adj-Ipsi) Finally, we tested whether a single, unified 4-ADC model provided better fit to the data than a combination of 2-AFC models for modeling decisions at each location (Chanes et al, 2013;Luo & Maunsell, 2018), (Fig. 1H).…”
Section: A Model For Predicting and Fitting Behavior In Multi-alternamentioning
confidence: 99%
“…Another key question for understanding attentional modulation of visual information is to identify the regions that drive these changes in processing, and when and how they influence visual cortical areas. There is evidence that some prefrontal cortical (PFC) regions are critically involved in visual attention and task-based modulations in response, including the frontal eye fields [34,35], the ventral prearcuate region [36], the superior precentral sulcus [37] and lateral PFC [38,39]. Selective prioritisation of task-relevant information in prefrontal cortex (e.g.…”
Section: Introductionmentioning
confidence: 99%